2008
DOI: 10.1353/dem.0.0015
|View full text |Cite
|
Sign up to set email alerts
|

Have we put an end to social promotion? Changes in school progress among children aged 6 to 17 from 1972 to 2005

Abstract: We examine trends over time in the proportion of children below the modal grade for their age (BMG), a proxy for grade retention, and in the effects of its demographic and socioeconomic correlates. We estimate a logistic regression model with partial constraints predicting BMG using the annual October school enrollment supplements of the Current Population Survey This model identifies systematic variation in the effects of social background across age and time from 1972 to 2005. While the effects of socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Several scholars have used proxies for retention based on the distribution of students’ grades of enrollment conditional on their ages (e.g., Bianchi, 1984; Frederick & Hauser, 2008; Hauser et al, 2007; Hauser, Pager, & Simmons, 2004; Heubert & Hauser, 1999). These proxies begin by observing whether students are enrolled in a grade below that which is modal for their age.…”
Section: How Many Students Are Retained?mentioning
confidence: 99%
See 2 more Smart Citations
“…Several scholars have used proxies for retention based on the distribution of students’ grades of enrollment conditional on their ages (e.g., Bianchi, 1984; Frederick & Hauser, 2008; Hauser et al, 2007; Hauser, Pager, & Simmons, 2004; Heubert & Hauser, 1999). These proxies begin by observing whether students are enrolled in a grade below that which is modal for their age.…”
Section: How Many Students Are Retained?mentioning
confidence: 99%
“…Our method was first introduced by Hauser, Frederick, and Andrew (2007); see also Frederick & Hauser (2008). We offer a number of technical improvements, provide estimates for a more recent and wider range of years, and validate the resulting measure against administrative record data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these limitations of NCES and CPS data, many scholars use proxies for retention based on the distribution of students’ ages within grades (e.g., Bianchi, 1984; Frederick & Hauser, 2008; Hauser, Frederick, & Andrew, 2007; Hauser, Pager, & Simmons, 2004; Heubert & Hauser, 1999). These proxies define students as “delayed” if they are enrolled below the modal grade for their age.…”
Section: Existing Measuresmentioning
confidence: 99%
“…In 2007, information from parent surveys suggested that 9.8 % of children in kindergarten through eighth grade had been retained (U.S. Department of Education, 2009) Hauser, Pager & Simmons (2004) examined grade retention data from other national sources and concluded that at least 15% of students aged 15-17 had been retained Hauser, Frederick & Andrews (2007) and Frederick and Hauser (2008) report increasing rates of grade retention over time. Although retention may add one year to children’s schooling, its largest cost may arise from the relationship between grade retention and later school dropout (Walberg, Reynolds, & Wang, 2004).…”
Section: Introductionmentioning
confidence: 99%